Emulsification properties of Puka Gum – An exudate of a native New Zealand tree (Meryta sinclairii): Effect of shear rate and Gum concentration. (March 2022) - Riana, Latifa Maulida; Sims, Ian M.; Matia-Merino, Lara
Abstract: This study investigated the effect of puka gum (PG) (crude and purified) concentration on its emulsification properties in terms of droplet size distribution, zeta potential, rheological and microstructural properties of the emulsions and their visual phase separation. Different concentrations of PG (1–10% w/w) were used to stabilize 15% w/w soybean oil-in-water emulsions. The effect of constant shear rate and time on the apparent viscosity of PG solutions was also tested. PG stabilised-oil-in-water emulsions exhibited monomodal size distributions with average droplet sizes ( d 32 ) below 2 μm at 4% w/w PG. The apparent viscosity of these emulsions was dependent on gum concentration exhibiting a Newtonian behaviour at low PG concentrations (≤4% w/w), with shear-thinning at higher concentrations, becoming slightly more pronounced above 100s −1 and especially at 10% w/w gum. The loss modulus ( G" ) was higher than the storage modulus ( G' ) at all concentrations indicating that the liquid-like behaviour dominated at all frequencies. The apparent viscosity of PG solutions, showed an irreversible loss of viscosity after shearing over a period of time, presumably resulting from chain breakage and molecular weight reduction. PG droplets were negatively charge with zeta-potential values in the range of −30 – (−45) mV. Furthermore, PG-stabilised emulsions remained stable against phase separation for at least 30 days. Crude and purified PG exhibited no major differences in terms of their emulsifying properties at 4% w/w suggesting that a purification process may not be required for food formulations. Overall, PG can be considered as a promising natural emulsifier for emulsion-based foods and beverage products. Graphical abstract: Image 1 Highlights: Crude (CPG) and purified puka gum (PPG) showed similar emulsification at 4% w/w. PG (4% w/w) could form emulsions of droplet sizes <2 μm and ζ-potentials around −30 mV. PG emulsions were stable against phase separation for at least 30 days at ≥4% w/w. Emulsions exhibited Newtonian to shear thinning behaviour with increasing PG. There was an irreversible viscosity loss of PG solutions under high shear.